ECO-AGROFORESTRY BUSINESS MADE BY COLLABORATION OF PT BUMN HIJAU LESTARI I AND ITS MITER FARMERS - Muhammad Arief Budiman; Nur Syamsiah; Pandi Pardian (UNEJ e-Proceeding, 2017)
Specially for Java and Bali, Citarum river stripe watering has an important role for Indonesianlife`s communities. However, along with the high population pressure and demand fornatural resources continues to increase, the level of pollution and environmental degradationin the watershed is increasing too. That requires prevention efforts as early as possible. Oneeffort to rehabilitate it is by eco-business agro-forestry. PT. BUMN Hijau Lestari I is one of thecompanies engaged in the greening of the environment (eco-business) based agro-forestryand cooperatives. The company is developing and helping local farmers to improve thewelfare of farmers as well as to prevention of environmental damage occurring in the upperCitarum Watershed. The purpose of this study was to determine how the strategy of thecompany, find an alternative development strategy and knowing what benefits could beobtained by partner farmers. The study was conducted in the Cimaung District, BandungRegency, West Java, which is one of the built area of PT. BUMN Hijau Lestari I which is locatedin areas along the Cisangkuy sub-watershed. Cimaung farmers are partners in representativedistrict and have managed to harvest the coffee from their agro-forestry that has beenrunning for 3 years. The design used are qualitative and quantitative with case studiesmethods by using an I-E analysis, SWOT analysis and QSPM for determining alternativedevelopment strategy of the company. Informant determination is done purposively. Dataanalysis shows that the company is using strategy with the seven principles of agro-forestryand cooperative. The results obtained score weighting environmental analysis of internalfactors 2.949 and 3.077 external factor score weights. This indicates that the company is incell II, which is growing and developing. So, the alternative strategies can be applied thatbased on the SWOT matrix and QSPM are expanded work area, maintaining quality ofproducts / services to attract the public, improve marketing and promotional activities,maintain cooperation with partner farmers and improve the quality and the quantity of theirhuman resources.